1054 GENDER DIFFERENCES IN MINOCA POPULATION. (15th December 2022) - Tattilo, Francesco Pio; Sansonetti, Angelo; Amicone, Sara; Bergamaschi, Luca; Armillotta, Matteo; Angeli, Francesco; Fabrizio, Michele; Stefanizzi, Andrea; Impellizzeri, Andrea; Canton, Lisa; Suma, Nicole; Bodega, Francesca; et al.
Abstract: Background: Myocardial Infarction with Non-Obstructive Coronary Arteries (MINOCA) is a clinical condition that includes acute myocardial infarction (AMI) occurring with non-obstructive coronary disease. This entity accounts above 6% (from 1% to 14%) of all patients presenting with AMI and it's known to be more prevalent in females. However, differences in terms of clinical features and prognosis in MINOCA patients according to gender have been poorly understood. Purpose: To evaluate differences in clinical characteristics at admission and during follow-up between males and females with MINOCA. Methods: We included all consecutive patients with AMI undergoing coronary angiogram between 2016 and 2020 at our center. According to 2016 ESC Position Paper criteria, we considered as MINOCA all patients with AMI and coronary stenosis <50% at coronary angiography without clinically apparent alternative diagnoses such as Takotsubo syndrome and myocarditis. Then, we analyzed the baseline clinical characteristics of MINOCA patients by dividing the population into two groups according to gender. Variables with a statistical significance lower than p<0.05 in univariable analysis were included in a logistic regression analysis to determine independent predictors of MINOCA. The predictive value of both groups was evaluated using Kaplan-Meier survival curves. Our aim was to evaluate composite endpoint of death, re IMA, stroke and heart failure in a follow up time mean of 36 ± 14.8 months. Results: Among 289 patients affected by MINOCA according to the 2016 ESC criteria, 98 were male (34%) and 191 were female (66%). Females were older than males (68.9 ± 13.1 vs 58.4 ± 14.5 years, p =0.0001). About the traditional cardiovascular risk factors males were more frequently smokers (56.1% vs 33.9%, p=0.001) while there were no significant differences in others risk factors. Females were more frequently on beta-blockers (39% vs 20%, p=0.002) and statins (33% vs 19%, p=0.015) compared to males. No differences were found between the two groups regarding clinical characteristics and instrumental findings (EKG and echocardiography). At coronary angiography, males had more frequently severe coronary stenosis than females (15.5 ± 26.4 VS 9.1 ± 21.5, p =0.019). During follow up we did not find any differences in terms of death, reinfarction, stroke and heart failure while females had more MACEs than males (33% vs 19.4%, p=0.015); and this data was confirmed at Kaplan Meier curves (p = 0.014). Finally, the multivariate analysis showed that age is an independent predictor of MINOCA (HR 1.04, CI 1.01-2.07, p=0.006), rather than sex, diabetes, and hypertension. Conclusions: In our MINOCA population we found that females were older than males, more frequently on statins and beta blockers at admission and they showed a lower degree of atherosclerotic disease. Nevertheless, after 36 ± 14.8 months of follow-up, we found a higher incidence of MACE in females than in males. We hypothesize that these findings could reflect the different pathogenesis of myocardial damage in our subgroups. Actually, statins and estrogens have a well-known protective role towards the progression of atherosclerosis, but they have no impact on other mechanisms of myocardial infarction which are more frequent in females, such as spontaneous coronary artery dissections, epicardial spasms or microvascular dysfunction.